2018
DOI: 10.4103/ijpvm.ijpvm_415_17
|View full text |Cite
|
Sign up to set email alerts
|

Predicting long-term cardiovascular events after transient ischemic attacks: Carotid artery intima-media thickness or ABCD2 score or both?

Abstract: Background:Patients who experienced transient ischemic attack (TIA) are at high-risk for cardiovascular events. This study aims to evaluate diagnostic value of carotid artery intima-media thickness (CIMT) and ABCD2 score for predicting cardiovascular events in long-term follow-up after TIA. We prospectively included sixty patients with TIA who admitted to hospital from March 2016 to August 2016.Methods:Duplex ultrasonography of internal carotid arteries was performed. ABCD2 scores were evaluated for each patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…For example, one study (72) showed that including CRP measurements in the acute phase to ABCD 2 improved the AUC significantly, but the TIA patient sample size was small and lacked validation. Other studies have also shown that adding parameters like DWI findings alone (44), brain infarction on DWI or CT (46), carotid imaging (at least 50% stenosis) and abnormal DWI (48), etiology and DWI (43, 71, 73), CT or transcranial Doppler (74), or carotid artery intima-media thickness (75) to ABCD 2 increase the c-statistics/AUC of ABCD 2 significantly. But many of these predictive models lack validation in large size cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…For example, one study (72) showed that including CRP measurements in the acute phase to ABCD 2 improved the AUC significantly, but the TIA patient sample size was small and lacked validation. Other studies have also shown that adding parameters like DWI findings alone (44), brain infarction on DWI or CT (46), carotid imaging (at least 50% stenosis) and abnormal DWI (48), etiology and DWI (43, 71, 73), CT or transcranial Doppler (74), or carotid artery intima-media thickness (75) to ABCD 2 increase the c-statistics/AUC of ABCD 2 significantly. But many of these predictive models lack validation in large size cohorts.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, ABCD 2 score has also been proposed as a useful tool to predict the occurrence of short‐term CI after TIA onset (Johnston et al., 2007). Until recently, the ABCD 2 score was the most widely used tool in predicting the occurrence of CI in clinical TIA patients (Cutting et al., 2016; Giles et al., 2017); however, its sensitivity and accuracy are still suboptimal in the short term of TIA (Khorvash et al., 2018). Thus, the methods to predict the risk of CI in TIA patients still need improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, the ABCD 2 score was the most widely used tool in predicting the occurrence of CI in clinical TIA patients (Cutting et al, 2016;Giles et al, 2017); however, its sensitivity and accuracy are still suboptimal in the short term of TIA (Khorvash et al, 2018).…”
Section: Introductionmentioning
confidence: 99%